Influence of efficacy values on the condition of winner or loser in numerical equality in male and female water polo - Iturriaga, F. A.; Marin, P. G.; Roque, J. I. A.; Lara, E. R. (International Journal of Computer Science in Sport, 2007)
The purpose of this study was to find efficacy values in playing microsituations in numerical equality with or without ball possession and to analyze the relation between these and the condition of winner or loser. The matches of the X World Championship of Water polo which did not end in a draw were analysed. Playing microsituations in numerical equality were evaluated by means of coefficients in order to obtain efficacy values. Some differences were revealed, in male category, in the following coefficients with possession: concretion, definition, resolution, accuracy and blocked shots received (p<.001) and precision (p=.001). Without possession: concretion, definition, resolution, accuracy and blocked shots made (p<.001) and precision (p=.001). In female category with the following coefficients with possession: concretion, definition and precision (p<001), resolution (p=.001), possibility (p=.005) and accuracy (p=.017). Without possession: concretion, definition and precision (p<.001), resolution (p=.001), possibility (p=.005) and accuracy (p=.017); taking as a reference a value of p<.05. To conclude, it can be said that in twelve out of the fourteen efficacy coefficients proposed for evaluating the playing microsituations in numerical equality with or without ball possession in male and female water polo there are significant differences between the condition of winner or loser.